Narratives of Chinese economic reforms: How does China cross the river? - Zhang, Xiaobo; Fan, Shenggen; de Haan, Arjan (World Scientific Publishing, 2010)
Rapid growth in the Chinese economy over the past three decades poses puzzles and challenges to neo-classical economic theory, as policies implemented during the reform process were often unorthodox. Although the Chinese experience has been widely studied, myths and questions about these reforms remain. To fill in the knowledge gap, and to inform a process of learning from China's development successes, this book features a series of case studies on the policy process of different initiatives, including rural industrialization, dual-track price reform, migration policy, village elections and fiscal reform.